The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1093/alcalc/agn072
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Concentrations in Antemortem Blood Samples Under Controlled Conditions

Abstract: Surprisingly, this study showed no ethanol production in improperly processed antemortem blood samples in healthy and sober individuals who were subjected to overnight fasting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 7 publications
1
10
0
1
Order By: Relevance
“…In one study loss of ethanol from opened tubes (mean 0.015 g/L) was greater than from unopened tubes (mean 0.010 g/L), after storage in a refrigerator for 13–39 months [17] . All bloods that were initially negative for ethanol content remained negative after short-term [22] and long-term storage under various conditions of time and temperature [15] , [17] .…”
Section: Discussionmentioning
confidence: 99%
“…In one study loss of ethanol from opened tubes (mean 0.015 g/L) was greater than from unopened tubes (mean 0.010 g/L), after storage in a refrigerator for 13–39 months [17] . All bloods that were initially negative for ethanol content remained negative after short-term [22] and long-term storage under various conditions of time and temperature [15] , [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Results of many studies have shown that microorganisms as found in our tested samples can cause glucose to ethanol conversion. 4,7,1214 So it is important to recognize that ethanol is formed as a result of the microorganisms’ action, not drinking an alcoholic beverage. Also, it is important to correctly interpret the urine ethanol concentration, especially if the blood sample was not taken.…”
Section: Resultsmentioning
confidence: 99%
“…The amount of generated ethanol depends on the species of microorganisms present, the available substrates, the temperature and time of storage, and the presence of preservatives added to the specimens. 3,4…”
Section: Introductionmentioning
confidence: 99%
“…Kanitin kommnasini saglamak için hasta giysiletini çikanrken odadan çikilmamahdir. Klinik alanlarda, kilidi hulunan camli ve rafli bir dolapta kanitlann teslim edilene kadar sakli tutulmasi kanitlann korunmasinda son derece önemlidir [38,39]. Kiyafetler olabildigince az katlanmah, sallanmamah ve yen degiçtirilmemelidir.…”
Section: C Elbiseler Ve Di § Ortaindan Biyolojik Numune Toplanmasiunclassified